2021
DOI: 10.1002/ddr.21870
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in trophoblast cell‐surface antigen 2 targeted therapy for solid tumors

Abstract: Trophoblast cell-surface antigen 2 (Trop 2) is a transmembrane glycoprotein that is highly expressed in various cancer types with relatively low or no baseline expression in most normal tissues. Its overexpression is associated with tumor growth and poor prognosis; Trop 2 is, therefore, an ideal therapeutic target for epithelial cancers. Several Trop 2 targeted therapeutics have recently been developed for the treatment of cancers, such as anti-Trop 2 antibodies and antibody-drug conjugates (ADCs), as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 115 publications
(131 reference statements)
0
13
0
1
Order By: Relevance
“…Previous studies have proved that trop2 is associated with tumor progression and the development of metastases ( Ripani et al, 1998 ; Bignotti et al, 2012 ; Trerotola et al, 2013 ). Trop2-targeted ADC drugs mainly include sacituzumab govitecan, PF-06664178, and datopotamab deruxtecan, of which sacituzumab govitecan and datopotamab deruxtecan have presented appealing clinical efficacy in solid cancers, while PF-06664178 has failed in a phase I trial ( Liao et al, 2021 ). The response rate of heavily pretreated metastatic triple-negative breast cancer patients who received sacituzumab govitecan-hziy was 33.3%, and the median overall survival was 13.0 months.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have proved that trop2 is associated with tumor progression and the development of metastases ( Ripani et al, 1998 ; Bignotti et al, 2012 ; Trerotola et al, 2013 ). Trop2-targeted ADC drugs mainly include sacituzumab govitecan, PF-06664178, and datopotamab deruxtecan, of which sacituzumab govitecan and datopotamab deruxtecan have presented appealing clinical efficacy in solid cancers, while PF-06664178 has failed in a phase I trial ( Liao et al, 2021 ). The response rate of heavily pretreated metastatic triple-negative breast cancer patients who received sacituzumab govitecan-hziy was 33.3%, and the median overall survival was 13.0 months.…”
Section: Discussionmentioning
confidence: 99%
“…Trophoblasts are the main component of the placental structure and play an important role in the formation of the placenta and the maintenance of the normal development of the fetus. In the early stage of blastocyst implantation, trophectoderm cells differentiate into two types of trophoblast cells, namely cytotrophoblast cells and syncytial trophoblast cells ( 20 ). In the early stage of blastocyst implantation, trophectoderm cells differentiate into two types of trophoblast cells, namely cytotrophoblast cells and syncytial trophoblast cells.…”
Section: Discussionmentioning
confidence: 99%
“…Varied studies have shown the involvement of Trop-2 in multiple growth-stimulating signaling pathways, thereby playing a role in the growth and proliferation of tumor cells. An increased expression level of Trop-2 is closely associated with a poor prognosis of various solid tumors [ 27 , 28 ]. Trop-2 has been selected as the prognostic marker or an attractive target to develop targeting molecules for diagnosis and tumor therapy.…”
Section: Discussionmentioning
confidence: 99%